MEWFM 2021
DOI: 10.5742/mewfm.2021.94154
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Associated Factors of Diabetic ketoacidosis among Patients Living with Type 1 Diabetes in Makkah Al-Mukarramah City

Abstract: Objective: To assess magnitude of diabetic ketoacidosis (DKA) among type-1 diabetics and to identify associated risk factors. Methods: A cross-sectional study was conducted among 236 type-1 diabetics in Makkah Al-Mukarramah City, Saudi Arabia. Results: Among participants, 59.3% were males, 44.1% were diabetic for more than 5 years, while 70.8% reported past history of DKA. The main causes of DKA were gfirst presentation of the diseaseh (40.9%), and gdiscontinued treatmenth (37%). The HbA1c among 53.6% wa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…Similarly, Saudi Arabia was also one of the countries with the highest rates of DKA at diagnosis of T1DM (59%) 8. In addition, several studies from Saudi Arabia reported highlighted poor glycaemic control as reflected by high HbA1c levels and increased prevalence of DKA among children and adolescents with T1DM 9–11…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Saudi Arabia was also one of the countries with the highest rates of DKA at diagnosis of T1DM (59%) 8. In addition, several studies from Saudi Arabia reported highlighted poor glycaemic control as reflected by high HbA1c levels and increased prevalence of DKA among children and adolescents with T1DM 9–11…”
Section: Introductionmentioning
confidence: 99%